Reliability analysis of the cast-in-place bored pile with different defects - Yao, Hua; Ma, Lemin; Duan, Zhiqiang; Guo, Wei (Frontiers in Built Environment, 2024)
The defects of the cast-in-place bored piles heavily influence their integrities and bearing capacities. The bearing capacity and reliability index of the cast-in-place bored piles with different defects were studied using the finite element method. The accuracy of the numerical model is verified by the field test results of an in situ cast-in-place bored pile. Parametric studies are conducted to investigate the toe debris, mud cake, and necking and bulging defects on the ultimate bearing capacities of the cast-in-place bored piles. The results indicate that maximum reduction in the ultimate bearing capacities of the cast-in-place bored pile was observed, with the ultimate bearing capacity of the toe debris defect decreased by 17%, that of the mud cake defect decreased by 19%, that of the necking defect by 6.1%, and that of the pile bulging defect increased by 40.9%. The minimum reliability index can be 0.81 when the diameter of the pile necking defect is 0.2 m. The maximum reliability index can be 3.63 when the diameter of the pile necking defect is 2.0 m.